Valued technical and non-technical skills among disaster responders: a cross sectional study of disaster responders involved in the earthquake in Türkiye and Syria January 2023 - Anja Westman; Lisa Kurland; Karin Hugelius (BMC Emergency Medicine, 2024)
Abstract Introduction Disaster responders are an important part of disaster response. However, despite large efforts to train disaster responders, there is a limited scientific knowledge regarding which competences and skills such responders value and lack during a real mission. The aim of this study was to investigate used and needed skills among disaster responders responding to the earthquake in Türkiye and Syria 2023 Methods A cross-sectional study using a non-randomized sample was conducted, collected between March and July, 2023. The participants were recruited through invitations distributed to international organizations, and the data were gathered through a web-based survey. The data were analyzed using descriptive and comparative statistics. Results A total of 525 participants involved in the disaster response in Türkiye or Syria in February 2023 were included. The most common valued skills were teamwork skills (n = 252, 59%), technical knowledge (n = 204, 48%), leadership skills (n = 105, 24%) and communication skills (n = 114, 17%). Women valued stress management (n = 33, 26%) more than leadership (n = 24, 19%) Technical knowledges were more valued among first-time responders (n = 168, 82%) compared to experienced responders (n = 108, 54%, p-value < 0.001). The most reported lacked skills were mental preparedness (n = 237, 53%), knowledge of the management system of international response (n = 132, 30%), stress management (n = 105, 24%) and leadership (n = 102, 23%). Conclusion The results showed slightly different needs in the various phases of a response, as well as some differences between men and women. Improving mental preparedness was not one of the most highly valued skills, but it was one of the skills that was most lacking; this discrepancy is an interesting finding. More in-depth analysis and additional studies are needed to further understand how best to prepare disaster responders and how their training can include the desirable skills. Further studies should be focused on the experience and knowledge of qualified disaster responders. This knowledge could also be of use when recruiting since several of the non-technical skills are not only gained solely through specific training.